Published Papers about Interior Design from South East Europe in the Scopus Database (1977 - 2015) - Nikoljski Panevski, Elena; Petanovski, Aleksandar; Spiroski, Ivo (Scientific Foundation Spiroski (publications), 2015)
AIM: The aim of this study was to analyse current scientific impact of Published Papers about Interior Design from South East Europe in the Scopus Database (1977-2015). MATERIAL AND METHODS: Title search of the Scopus database was performed on October 02, 2015 about interior design from South East Europe in the Scopus Database (1960-2014). A total number of 5,808 documents worldwide were identified with "interior design" in the title, abstract or keywords. By limitation to South East European countries (Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Cyprus, Greece, Kosovo, Moldova, Macedonia, Montenegro, Romania, Serbia, Slovenia, Turkey, and Italy) only 151 documents were separated (2.6% of all documents). Selected documents were analysed by year, source, author, country/territory, document type, and subject area. RESULTS: The number of publication in the period of 1977-2005 year was very small and was increased with maximum of 19 papers in 2011 year. Three academic journals published most of the papers: Medicina Del Lavoro (14 papers); Work and Design Principles (5 papers), and Practices (4 papers). The biggest number of papers belongs to the author Nicoletti S with 6 papers, followed by Di Leone G, Carino M, Trani G, and Yildirim K (5 papers each). Universities from Turkey and Italy are dominant institutions which published academic papers. Prevalence of the published papers about interior design from South East Europe in the Scopus Database (1977-2015) was from Italy (67 papers), Turkey (55 papers), and Croatia (10 papers). Most of the documents published about Interior Design from South East Europe were articles and conference papers. Subject area medicine was predominant followed by engineering, social sciences, and others. CONCLUSION: Officials of the academic institutions in South East European countries should undertake more effective and proactive policies in order to include more journals in the Scopus database.
Keywords: interior design; Scopus database; citation metrics; South East Europe